2022
DOI: 10.1111/bjh.18530
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of transplant outcomes between haploidentical transplantation and single cord blood transplantation in non‐remission acute myeloid leukaemia: A nationwide retrospective study

Abstract: SummaryAllogeneic haematopoietic stem cell transplantation (HSCT) is a potentially curative treatment for some patients with acute myeloid leukaemia (AML) who are refractory to chemotherapy. Cord blood transplantation (CBT) is a reasonable option in such cases because of its rapid availability. Recently, a growing number of human leucocyte antigen (HLA)‐haploidentical related donor HSCTs (haplo‐HSCTs) have been performed, although its effectiveness remains undetermined. Using the Japanese nationwide transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…1 Our study analysed propensity score-matched pairs of patients with acute myeloid leukaemia (AML) in non-remission who underwent CBT or haploidentical haematopoietic stem cell transplantation (haplo-HSCT). 2 The study results showed that outcomes were comparable for CBT and haplo-HSCT overall, but subgroup analysis restricted to patients using MAC showed significantly better overall survival with CBT.…”
Section: Cord Blood Versus Haploidentical Transplantations For Non-re...mentioning
confidence: 87%
“…1 Our study analysed propensity score-matched pairs of patients with acute myeloid leukaemia (AML) in non-remission who underwent CBT or haploidentical haematopoietic stem cell transplantation (haplo-HSCT). 2 The study results showed that outcomes were comparable for CBT and haplo-HSCT overall, but subgroup analysis restricted to patients using MAC showed significantly better overall survival with CBT.…”
Section: Cord Blood Versus Haploidentical Transplantations For Non-re...mentioning
confidence: 87%
“…Lower probability of relapse after myeloablative cord blood transplantation for patients with refractory AML Matsuda et al 1 recently described the outcomes of patients with 'non-remission' acute myeloid leukaemia (AML) after haematopoietic stem cell transplantation (HSCT) using readily available alternative donors: cord blood (CB) and haplo-identical (Haplo) donors. This very well written manuscript, however, did not emphasize an important finding: that patients with active disease who received a myeloablative CB transplant had an approximately 1.5-fold higher probability of survival compared to those with haplo-donors.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…Since these transplants are urgent, rapidly available donor sources are required, and these include CB and haplodonors. The paper of Matsuda et al 1 describes a retrospective comparison of outcomes of recipients of unrelated CB grafts (n = 918) and those of haplo-HSCT (n = 459) from the Japanese Registry. These two groups were selected of a total of 2438 'non-remission' AML patients with ages of 16-65 years transplanted during the period January 2008-December 2018, after 2:1 propensity matching.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue Matsuda et al report on the largest retrospective registry study comparing the outcomes of not‐in‐remission acute myeloid leukaemia (AML), allografted with single cord blood (sCB) or haploidentical donor 1 …”
mentioning
confidence: 99%